Pre-treatment with cyproterone acetate plus ethinylestradiol enhances ovarian response in women with polycystic ovary syndrome - Chowdhury, Priyanka; Banu, Jesmine; Deeba, Farzana; Debnath, Rajib Chandra; Rani, Chalontika; Sultana, Sharmin; Ishrat, Shakeela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anti-mullerian hormone (AMH) and androgen levels are higher in women with polycystic ovary syndrome (PCOS) than norm-ovulatory women. Cyproterone acetate plus ethinylestradiol (CPA+EE) reduces AMH and free androgen level. The aim of the study was to determine if the pretreatment with CPA+EE before ovulation induction with letrozole improves ovarian response in PCOS women. Methods: The study comprised of 100 infertile PCOS women with serum AMH>5 ng/ml. The study participants were randomly allocated into women given CPA+EE pretreatment cyclically for 3 months before ovulation induction with letrozole 5 mg from day 2-6 of a menstrual cycle, and women given only letrozole from day 2-6 without any pretreatment. Follicular growth was monitored by transvaginal sonography on day 12. Women who attained maximum follicular size (18-25 mm) were given 5000 IU HCG injection. Ovulation was confirmed by serum progesterone assay on day 21-23 and pregnancy was confirmed by serum β-hCG level or by pregnancy test kit. Results: Ovulation rate was higher (82.4%) in pre treatment group compared in letrozole only group to (43.0%) with relative risk 1.92. Pregnancy rate was higher in (23.5%) in pre treatment group than letrozole only (8.8%) with relative risk 2.68. Conclusions: Pretreatment with CPA+EE before ovulation induction with letrozole has better outcome in terms of ovulation and pregnancy than letrozole alone in PCOS women with high serum AMH.